Public market information system and farmers food marketing decisions: econometric evidence from Benin - Kpenavoun Chogou, Sylvain; GANDONOU, AHOUIGNANDJI ESAÏE (My University, 2012)
To sell the surpluses of maize, the main staple in Benin, farmers could choose among three modes of transaction: they could sell under a contract with itinerant traders, or sell without a contract at the farm gate or on distant markets. It has been postulated that farmers will choose a profitable mode of transaction if they receive reliable market information on the prevailing market conditions. Using detailed farm household survey data from Benin, this paper applied the Nested Logit model to test this hypothesis. The results showed that farmers will opt to sell at the farm gate without a contract if they receive market information and use it to plan their market transactions. However, such a decision was not related to the reception of market information channeled through the government supported ‘Market Information System' but rather to information obtained from the farmers’ personal or professional networks.
Keywords: Farmers; modes of transaction; liberalization; public market information system.